The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/meg.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

String esophageal capsule endoscopy with real-time viewing improves visualization of the distal esophageal Z-line

Abstract: Compared with ECE, SECE+RTV provides a better view of the distal esophagus in healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…However, these results were not validated by another string capsule study, which showed sensitivity and specificity of 84% and 72%, respectively [ 106 ]. Nevertheless, it has been shown that string capsule endoscopy improves visualization of the distal esophagus, which may potentially have an impact on the detection of esophageal varices [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, these results were not validated by another string capsule study, which showed sensitivity and specificity of 84% and 72%, respectively [ 106 ]. Nevertheless, it has been shown that string capsule endoscopy improves visualization of the distal esophagus, which may potentially have an impact on the detection of esophageal varices [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al introduced string ECE with real-time viewing [ 32 ]. They evaluated the cotton string-attached PillCam ESO capsule in 30 healthy volunteers with a real-time monitoring program.…”
Section: Additional Applicationsmentioning
confidence: 99%
“…They evaluated the cotton string-attached PillCam ESO capsule in 30 healthy volunteers with a real-time monitoring program. Compared with conventional ECE, the string-attached ECE showed improved Z-line visualization (at least two-quadrant visualization, 100.0% vs. 80.0%, p <0.001; at least three-quadrant visualization, 90.0% vs. 36.7%, p <0.001) [ 32 ].…”
Section: Additional Applicationsmentioning
confidence: 99%
“…16 The stringed esophageal wireless capsule endoscopy is considered to improve the operability and diagnostic yield in the identification of esophageal pathology. 17 In addition, the capability of the wireless device for providing the retrograde view of certain anatomical structures of the esophagus [e.g., the upper and lower esophageal sphincter (LES)] would be desirable for both clinical and research purposes.…”
Section: Introductionmentioning
confidence: 99%
“…If the capsule is attached to the strings as is described in Ref. 17, the mucus is trapped between the strings during the retrograde scanning and it makes capturing an image impossible. The retrograde scanning can provide new information on the esophageal pathology.…”
Section: Introductionmentioning
confidence: 99%